Unfair Competition by Government Firms and Authorities in the Consulting Market - Roger Svensson (The Research Institute of Industrial Economics (IUI), 2001)
Government firms and authorities often sell services in the free market via affiliated consulting firms (CFs). In this study, I analyze whether these agents have an unfair competitive edge compared to private CFs. The theoretical analysis shows that private and state-owned CFs operate under different conditions. A private CF must choose between having permanent employees and pay full-time wages with the risk of over- and under-capacity or hiring professionals temporarily in the free market, which gives flexibility but may cause problems in hiring qualified professionals. In contrast, state-owned CFs can hire professionals from their parents and have the exclusive right to do so. With experiences from Sweden, I show that this exclusive dealing contract is a schoolbook example on unfair competition and gives several negative welfare effects and consequences. First, private CFs profits are lowered. In some cases, private CFs are deterred from entering the market. Second, competition is limited, meaning that the buyers of consulting services are worse off. Third, a necessary reorganization of the Swedish consulting sector is prevented. Fourth, the unfair competition is the main reason why the re-flow to Sweden from multilateral development agencies has been so low during the recent 20 years. This last consequence is especially analyzed.
Keywords: H40; L30; L80; 330; State-Owned Consulting Firms; Unfair Competition; Exclusive Dealing Contracts; Re-Flow from Multilateral Development Agencies; Unternehmensberatung; Öffentliches Unternehmen; Wettbewerbsbeschränkung; Schweden